Linear polarization of x-rays emitted in the decay of highly-charged ions via overlapping resonances. (November 2015) - Wu, Z W; Surzhykov, A; Kabachnik, N M; Dong, C Z; Fritzsche, S
Abstract: The linear polarization of x-rays, emitted from highly-charged ions, has been studied within the framework of the density matrix theory and the multiconfiguration Dirac-Fock method. Emphasis was placed especially on two-photon cascades that proceed via intermediate overlapping resonances. For such two-step cascades, we here explore how the level-splitting of the resonances affects the linear polarization of the x-rays, and whether modifications in the degree of polarization may help determine small level-splittings in multiply- and highly-charged ions, if carefully analyzed along isoelectronic sequences. Detailed calculations are carried out for the 1 s 2 p 2 Ji = 3/2 → 1 s 2 s 2 p J = 1/2, 3/2 + γ1 → 1 s 2 2 s Jf = 1/2 + γ1 + γ2 radiative cascade of lithium-like W 71+ ions. For this cascade, a quite remarkable increase of the (degree of) linear polarization is found for the second-step γ2 photons, if the level-splitting becomes smaller than Δω ≲ 0.2 a.u. ≈ 5.4 eV. Accurate polarization measurements of x-rays may therefore be also utilized in the future to ascertain small level-splittings in multiply- and highly-charged ions.